An Assessment of Right Hepatic Artery Variations Using Contrast-enhanced Computed Tomography Angiography - Mahadev Sidram Shiraganve; Veereshkumar S. Shirol; Virupaxi V. Hattiholi; Sheetal V. Pattanshetti (Journal of the Scientific Society)
Background: Lipshutz B. began studying hepatic artery variations in 1917 and described the variations in the celiac artery and its branches. The continuation or unusual regression of parts of the early blood vessel system is responsible for these variations. A thorough preoperative evaluation of the source and branching configuration of the right hepatic artery (RHA) is essential for effective resections related to the right hepatic lobe due to the significant variability in the vascular structure of the right intrahepatic region. Aim/Objective: The aim is to investigate the origin of the RHA and to assess variations in its origin by using contrast-enhanced computed tomography (CT) angiography. Materials and Methods: This case series study was conducted in the radiology and imaging unit of KLES Dr. Prabhakar Kore Charitable Hospital and Medical Research Centre, Belagavi. The study included 578 patients, consisting of 360 males and 218 females between the ages of 7 and 80 years. CT abdominal angiograms using the GE Revolution EVO 128 Slice were utilized to identify the origin of the RHA. Results: The proper hepatic artery is the predominant source of the RHA in 545 cases (94.3%) of; however variations occur, with 26 cases (4.5%) showing an RHA originating from a superior mesenteric artery, in 5 cases (0.9%) RHA directly from the aorta, and 2 cases (0.3%) originating from the gastroduodenal artery. Conclusion: Variations in the RHA can be evaluated with the help of 128-slice multidetector computerized tomography. Vascular architecture can be clearly visualized due to high-resolution capabilities, which are essential for interventional operations and preoperative planning.